A Deadline-Constrained Scheduling Algorithm for Intensive-Instance Serviceflows in Cloud Environment - Wei Liu; Taoshen Li; Ruwei Huang (Dianxin kexue)
The problem that there are many intensive-instance serviceflows in business cloud computing environment was aimed to solved, so a new two-phase serviceflows scheduling algorithm was proposed. In the first phase, the global deadline to each instance was assigned, and then the deadline to the each task of instances was assigned. In the serviceflows execution phase, in order to solve the possible problem of time exception which task was not meet its sub-deadline, the algorithm adjusted deadlines of subsequent task dynamically. The experimental results in CloudSim show that the algorithm compared with others algorithm saves the execution cost with meeting the user-defined deadline, avoids the fierce competition of cheaper services and improves the success ratio of the scheduling.